PROTOTIPE SISTEM KENDALI ENGKOLL PADA KAMERA GAMMA BERBASIS WIRELESS - Azis Frady Hutabarat; Yohannes Yohannes; Rachmat Ramdani (JURNAL TEKNOLOGI INDUSTRI, 2019)
In rocket manufacturing, it is very important to pay attention to the quality of the materials used. To test the material, it is carried out by means of a radiographic test, which is a test that is carried out without damaging the material, either physically or by chemical reactions of the material. For now, the radiographic test is still manual so it is dangerous.In some cases, there is a lack of safety in the radiography process. Such as the high level of radiation exposure, which is received by the operator (human), is due to manual testing. This is very dangerous, because the impact cannot be felt directly, but will have a long impact. Therefore an automatic gamma camera crank control system was made in the radiography process based on Arduino Uno which can be done using a remote control, so as to minimize the radiation exposure received by the operator.From the experimental results of the tool made, it shows that the remote control can work properly using radio frequencies up to a distance of 25 m.Keyword : radiografi test, radiasi sinar gamma, arduino uno, radio frekuensi